دراسة تأثير نسبة المواد الناعمة على السلوكية الانضغاطية للترب الرملية - منذر الزاوي; صفوان عبدالله; عمار النمر (Tishreen University, 2018)
تتأثر سلوكية التشديد في الترب الرملية غير الصافية بشكل كبير بنسبة المواد الناعمة التي تدخل فيها وتتبدل تبعا لذلك بارامترات التشديد, ومن أجل دراسة هذه الظاهرة تم مخبريا تشكيل مجموعة من عينات الترب المختلطة(رمل مضاف اليه نسب مختلفة من المواد الناعمة السيلتية), وأجريت عليها تجارب التشديد لدراسة تأثير تغير نسب الخلط على تشديد هذه العينات, وقد بينت نتائج الاختبارات المجراة أن نسبة المواد الناعمة المضافة إذا كانت ضمن مجال معين اصطلح على تسميته بالمجال الانتقالي لا تكون التربة المختلطة فقط منخفضة الانضغاطية بل يتحسن تماسكها لأن المواد الناعمة عند نسبة معينة تملأ الفراغات بالكامل وهو ما يبرهن ان الترب المفككة اذا كانت فيها نسبة المواد الناعمة قريبة من المجال الانتقالي فان انضغاطيتها لن تزيد , كما بينت النتائج ان المجال الانتقالي المثالي للمواد الناعمة هي في حدود 10%-15% وهذا يتوافق مع العديد من الأبحاث المجراة في هذا المجال. Consolidation behavior of pure sandy soil is significantly affected by the percentage content of fine materials, which controls the parameters of Consolidation. In order to study this phenomenon, it was formed a set of mixed soil samples at laboratory (by adding to the sand, different percentages of fine materials), and then consolidation tests were carried out to study the effect of changing the mixing percentage. The results of tests have demonstrated that the percentage of fines additives if they are within a limited range has been termed transitional range, at which mixed soil not only has a low compressibility but also an improvement in its cohesion is occurred. Because the fine material at a certain percentage completely fills the spaces which proves that if the percentage of fine material in the cohesionless soil close to the transition percentage, the compressibility will not increase. The results also showed that the ideal transition range for fine materials are in the range of 10% -15%, and those values are in a good agreement with many of the researches that were conducted in this domain.